Gene Expression Analysis of Three Putative Copper-Transporting ATPases in Copper-Tolerant Fibroporia radiculosa - Katie M. Ohno; Amy B. Bishell; Glen R. Stanosz (Frontiers in Microbiology, 2020)
Copper tolerance of brown-rot basidiomycete decay fungi can lessen the efficacy of copper-containing wood preservatives for wood products in-service. The purpose of this study was to evaluate wood mass loss and differential expression of three genes that have putative annotations for copper-transporting ATPase pumps (FIBRA_00974, FIBRA_04716, and FIBRA_01430). Untreated southern pine (SP) and SP treated with three concentrations of ammoniacal copper citrate (CC, 0.6, 1.2, and 2.4%) were exposed to two copper-tolerant Fibroporia radiculosa isolates (FP-90848-T and L-9414-SP) and copper-sensitive Gloeophyllum trabeum isolate (MAD 617) in a 4-week-long standard decay test (AWPA E10-19). Decay of copper-treated wood was inhibited by G. trabeum (p = 0.001); however, there was no inhibition of decay with increasing copper concentrations by both F. radiculosa isolates. Initially, G. trabeum and one F. radiculosa isolate (L-9414-SP) highly upregulated FIBRA_00974 and FIBRA_04716 on copper-treated wood at week 1 (p = 0.005), but subsequent expression was either not detected or was similar to expression on untreated wood (p = 0.471). The other F. radiculosa isolate (FP-90848-T) downregulated FIBRA_00974 (p = 0.301) and FIBRA_04716 (p = 0.004) on copper-treated wood. FIBRA_01430 expression by G. trabeum was not detected, but was upregulated by both F. radiculosa FP-90848-T (p = 0.481) and L-9414-SP (p = 0.392). Results from this study suggest that all three test fungi utilized different mechanisms when decaying copper-treated wood. Additionally, results from this study do not provide support for the involvement of these putative gene annotations for copper-transporting ATPase pumps in the mechanism of copper-tolerance.